Near‐peer bedside clinical teaching: example of a successful programme. (October 2014) - Woods, Robbie; Ramasubbu, Ben; Donohoe, Claire; Hennessy, Martina
Summary Background Traditionally, the formalised teaching of medical students has begun at senior trainee level, with teaching from junior trainees being very limited and informal. A pilot programme was set up in a large university teaching hospital for interns to provide structured bedside clinical teaching to final‐year medical students as an adjunct to their formal teaching. Derived from the success of this, a similar programme was run the following year. Methods Feedback from the pilot programme and its successor was evaluated using a five‐point Likert scale, and open illustrative comments were also collected. Results There was a highly positive response to the initial programme, with final‐year students being very positive about participating as teachers the following year. Some proceeded to run the programme the following year, providing feedback to suggest improvements on the pilot programme. Discussion Junior trainees can organise and provide an additional option to traditional formal undergraduate clinical bedside teaching, which is well received by students. It also provides a forum through which trainees can hone teaching methods and improve clinical skills. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> A programme was set up for interns to provide structured bedside clinical teaching to final‐year medical students </boxed-text>